Internet connectivity disruption in Egypt (Egypt) - Voidly (2026)
CRITICAL severity disruption detected in Egypt. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: EG-2026-0134
Keywords: internet disruption; EG; disruption; critical